Misconduct in public office: an appraisal of legal perspective in Malaysia / Wan Murshida Wan Hashim and Mazlena Mohamed Hussain - Wan Hashim, Wan Murshida; Mohamed Hussain, Mazlena (Universiti Teknologi MARA, 2021)
Misconduct in public office or known as MIPO is a common law offence of which reference is made to any wrongdoing or misbehavior committed by public official. The MIPO does not confine to any specific offences as it covers all sorts of wrongdoings either minor or major. The public official who commits any offences of MIPO shall be liable for criminal, civil or disciplinary action. This paper analyses the offence of MIPO under the common law and Malaysian law perspective. The objective of this paper is to provide an insight into the legal mechanism applied in Malaysia in relation to the misconduct committed by public officials. It shall also provide a preliminary view on the extent to which the existing laws are able to deter misconduct amongst public officials. This is a doctrinal research whereby analysis is purely based on documents i.e. legal text and doctrine, thus no empirical data is used for discussion. The findings revealed that it is vital for the existing laws to be amended accordingly so that the MIPO could be addressed effectively and efficiently.